1995
DOI: 10.1037/0735-7044.109.5.859
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in learning and memory in mice: Effects of sequence of testing and cholinergic blockade.

Abstract: Sexual dimorphism in spatial and cued navigation using the Morris water maze was examined in C57BL/6 mice both with and without administration of scopolamine, a cholinergic blocker. In Exp. 1, female and male mice learned to perform first a spatial, then a cued, navigation task. Both performed a spatial task similarly; males, however, performed a cued task better than females. In Exp. 2, the sequence of navigation testing was reversed. Both performed similarly on a cued task; however, males performed a spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
39
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 69 publications
9
39
0
Order By: Relevance
“…In spite of the fact that some studies have shown sex differences in inhibitory avoidance in non-treated animals (e.g. 25), our results (no sex differences) agree with those published by Lamberty and Gower (36) and Berger-Sweeney et al (37). In our laboratory, sex differences in inhibitory However, subtle differences between males and females were present in our study.…”
Section: Discussionsupporting
confidence: 74%
“…In spite of the fact that some studies have shown sex differences in inhibitory avoidance in non-treated animals (e.g. 25), our results (no sex differences) agree with those published by Lamberty and Gower (36) and Berger-Sweeney et al (37). In our laboratory, sex differences in inhibitory However, subtle differences between males and females were present in our study.…”
Section: Discussionsupporting
confidence: 74%
“…Thus, our data support an emerging understanding that sexual dimorphism in the brain is not limited to limbic or endocrine areas, but extends into cognitive centers of the brain, including cerebral cortex (see for example, Clarke and Goldman-Rakic, 1989;Desmond and Levey, 1997;Juraska, 1991;McEwen et al, 1997;Toran-Allerand, 1991). Dimorphic cortical structures as well as hippocampal structures may in fact be the substrate for the long observed dimorphisms in the performance of spatially oriented behavioral tasks (Berger-Sweeney et al, 1995;Gaulin and Hoffman, 1988;Halpern, 1992;Williams and Meck, 1991).…”
Section: Figuresupporting
confidence: 69%
“…Differences in learning, activity, and anxiety-related behavior between male and female mice from common inbred strains are well documented (Berger-Sweeney et al, 1995;Bolivar et al, 2001;Voikar et al, 2001;Jonasson, 2005). Notably, there are also behavioral and neurochemical differences between hemizygous male and homozygous female fmr1 KO mice Braun, 2001, 2004;Qin et al, 2005).…”
Section: Discussionmentioning
confidence: 98%